Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environments – when there is scope to trial and adapt programme strategies. So argues Amir Allana in Navigating Complexity, a case study of Northern Karamoja's Growth, Health and Governance (GHG) Programme that is adopting an 'adaptive management' approach. This BEAM Exchange webinar invited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from their work in Uganda and Cambodia. What does adaptive management look like in practice? And what does it require of managers and funders to make it happen? Tim and Peter share their experiences of applying adaptive management techniques to the Growth, Health and Governance Programme and the Cambodia Agricultural Value Chain Program (CAVAC). Amir highlight insights from the Navigating Complexity report, including the importance of office culture, consistent management signals, and the role of supportive tools and processes.